Increased Buying Interest of Millennial Generation in Gresik Regency during the COVID-19 Pandemic through the @kulinergresik account - Didiek Tranggono; Putri Musicasari; Zainal Abidin Achmad (Universitas Islam Balitar, 2021)
The Instagram account @kulinergresik experienced an increasing number of followers along with the increase in the number of food orders, during the COVID-19 Pandemic. This study intends to analyze whether there is a relationship between pandemic conditions and as an independent variable with the purchase interest of the millennial generation of Gresik Regency on the account @kulinergresik as the dependent variable. The quantitative research method uses Spearman rank correlation analysis and t-test for the hypothesis. The study population was 144,000 followers of the @kulinergresik account with purposive sampling and data collection through the distribution of google form as a questionnaire to 100 respondents. The results showed that between the two research variables had a correlation coefficient of 0.389, meaning that it indicated a positive relationship. Besides, the results of t-test showed a 5% significance level, and it has a meaning that the hypothesis accepted. In conclusion, during the COVID-19 Pandemic, millennial generation buying interest through the @kulinergresik account has increased.